All he'll ever need - Lough, Loree (Lough, Loree. Little child shall lead them., 2019)
For Amish widower Phillip Baker, providing for his family in the wake of his wife's death means back-breaking work and renewed dedication to his faith. Still, his strength can<U+2019>t help him relate to his little son<U+2019>s struggles. It seems a godsend when new doctor Emily White is able to treat Gabe<U+2019>s shyness and fear even as she helps heal him. But no matter how strongly Phillip is drawn to the caring Englisher from the city, their differences may be too great to overcome . . . Reeling from her own tragic loss, Emily keeps loneliness at bay through her clinic work. Somehow, though, Gabe and his gentle, sad-eyed father are making her want to risk opening her heart again. But can she find acceptance in their Plain world<U+2014>and a way to turn their separate lives into a family forever? . . .